Ein Fürstenleben zwischen Alltag und Aufruhr: Die französische Korrespondenz (1772-1801) des letzten Salzburger Fürsterzbischofs Hieronymus Colloredo mit seinem Bruder Gundaker - Lobenwein, Elisabeth (2021)
Hieronymus Colloredo (1732-1812) was Salzburg's Prince Archbishop between 1772 and 1803. He corresponded with his brother, the imperial vice-chancellor Gundaker Collordo (1731-1807). A total of 655 letters have been preserved, most of them from the years 1790 to 1800.